Taxonomic review of the genus Spatulignatha Gozmány, 1978 (Lepidoptera: Lecithocerinae), with descriptions of two new species in China - Liu, Shurong; Wang, Shuxia (Zootaxa, 2014)
The genus Spatulignatha Gozmány is reviewed. Two new species are described based on the Chinese material: S. arcuata sp. nov. from Guangdong, Hunan and Yunnan, and S. longizonalis sp. nov. from Guangxi. The female genitalia of S. hemichrysa (Meyrick, 1910) and the female of S. idiogena Wu, 1994 are described for the first time, and the previously described female of S. hemichrysa by Gozmány (1978) is considered to be the female of S. olaxana Wu, 1994. Images of adults and genitalia are provided.